Impact of Patient Affect on Physician Estimate of Probability of Serious Illness and Test Ordering. (November 2017) - Kline, Jeffrey A.; Neumann, Dawn; Raad, Samih; Schriger, David L.; Hall, Cassandra L.; Capito, Jake; Kammer, David
Abstract : Purpose: The authors hypothesize patient facial affect may influence clinician pretest probability (PTP) estimate of cardiopulmonary emergency (CPE) and desire to order a computerized tomographic pulmonary angiogram (CTPA). Method: This prospective study was conducted at three Indiana University–affiliated hospitals in two parts: collecting videos of patients undergoing CTPA for suspected acute pulmonary embolism watching a humorous video (August 2014–April 2015) and presenting the medical histories and videos to clinicians to determine the impact of patient facial affect on physicians' PTP estimate of CPE and desire to order a CTPA (June–November 2015). Patient outcomes were adjudicated as CPE+ or CPE− by three independent reviewers. Physicians completed a standardized test of facial affect recognition, read standardized medical histories, then viewed videos of the patients' faces. Clinicians marked their PTP estimate of CPE and desire for a CTPA before and after seeing the video on a visual analog scale (VAS). Results: Fifty physicians completed all 73 videos. Seeing the patient's face produced a > 10% absolute change in PTP estimate of CPE in 1, 204/3, 650 (33%) cases and desire for a CTPA in 1, 095/3, 650 (30%) cases. The mean area under the receiver operating characteristic curve for CPE estimate was 0.55 ± 0.15, and the change in CPE VAS was negatively correlated with physicians' standardized test scores ( r = −0.23). Conclusions: Clinicians may use patients' faces to make clinically important inferences about presence of serious illness and need for diagnostic testing. However, these inferences may fail to align with actual patient outcomes. Abstract : Supplemental Digital Content is available in the text.